UPAYA PENINGKATAN PENGETAHUAN LANSIA TENTANG HIPERTENSI DI DESA ALUE KEUMANG KECAMATAN PANTE CERMIN KABUPATEN ACEH BARAT - Sufyan Anwar; Jun Musnadi; Marniati Marniati; Khairunnas Khairunnas; Ihsan Murdani (LPPM Universitas Wijaya Putra, 2023)
The aim of this program is to increase the knowledge of the elderly about the definition of blood pressure, hypertension, risk factors for hypertension, symptoms, impact and ways to prevent and treat hypertension. This activity is important to carry out because the distance between the village and the Public health center (Puskesmas) is about 5 km and the initial survey showed that more elderly people did not know about hypertension. Elderly (age ≥60 years) (18 people) and the volunteers of elderly integrated services post (Posyandu) (6 people) in Alue Keumang village were the targets of community service activities. Implementation on Sunday, 18th of September 2022 from 10.00 to 12.00 WIB at the village hall. The method used in carrying out the activity is lecture and discussion. The results showed that the enthusiasm of the participants to participate in education activity was very good. There was an increase in the participants' knowledge about hypertension, where some participants were able to answer correctly the questions posed by the presenter after the presentation was made compared to when the material was not delivered.